Late neurocognitive sequelae in patients with WHO grade I meningioma. Issue 8 (24th July 2008) - Dijkstra, M; van Nieuwenhuizen, D; Stalpers, L J A; Wumkes, M; Waagemans, M; Vandertop, W P; Heimans, J J; Leenstra, S; Dirven, C M; Reijneveld, J C; Klein, M
Abstract : Background: Information on neurocognitive outcome following treatment of benign meningiomas is virtually lacking. This is remarkable considering that survival in these patients is the most favourable of all intracranial tumours. The aim of the present study was therefore to document the extent and nature of neurocognitive deficits in patients with World Health Organization (WHO) grade I meningioma after treatment. Methods: 89 patients with WHO grade I meningioma who underwent surgery with or without adjuvant radiotherapy were individually matched to 89 healthy controls for age, sex and educational level. Neurocognitive functioning of patients was assessed at least 1 year following treatment and compared with that of healthy controls using the Student's t test. Additionally, associations between tumour characteristics (size, lateralisation and localisation), treatment characteristics (radiotherapy) and epilepsy burden (based on seizure frequency and antiepileptic drug use) and neurocognitive functioning were investigated. Results: Compared with healthy controls, patients with meningioma showed significant impairments in executive functioning (p<0.001), verbal memory (p<0.001), information processing capacity (p = 0.001), psychomotor speed (p = 0.001) and working memory (p = 0.006). Patients with skull base meningiomas performed significantly lower on three out of six neurocognitive domains compared with convexity meningiomas. Left-sided as opposed to right-sided meningiomas were related to verbal memory deficits. A higher epilepsy burden was significantly associated with lower executive functioning which primarily could be attributed to antiepileptic drug use. No significant associations were established between neurocognitive status and radiotherapy or tumour volume. Conclusions: Meningioma patients are characterised by long term deficits in neurocognitive functioning that can partly be attributed to the use of antiepileptic drugs and tumour location but not to the use of radiotherapy.